Determination of the radiation dose rate and radiogenic heat production of North Gabal Abu Hibban area, central Eastern Desert, Egypt. Issue 1 (2nd January 2019) - Elsadek M. Sabra, Mohamed; Abdeldayem, Abdelaziz L.; Youssef, Mohamed A. S.; Masoud, Alaa A.; Mansour, Salah A.
ABSTRACT: Airborne gamma-ray spectrometric data for Gabal Abu Hibban area, central Eastern Desert, Egypt have been used for assessment of the radiation dose rate and recognize radiogenic heat production (RHP). The radioelement concentrations of eU (ppm), eTh (ppm) and K (%) were used to ascertain such rates for the rock units. Results showed several levels of radiation as follow; (less than 0.50 mSv/yr), (from 0.50 to 0.70 mSv/yr) and (from 0.70 to 2.5 mSv/yr). The dose rate more than 1 mSv/yr is considered the radioactivity hazard level which represented mainly with Mu'tiq group, Younger granite, Trachyte rocks and Duwi Formation. RHP calculations have been carried out for the various rock units to locate the highest radiogenic heat production. The rock units that possess relatively huge RHP are Mutiq group, Younger granite and Trachyte rocks with values more than 3 μWm -3 .